2007
DOI: 10.1037/1931-3896.1.2.61
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in preferences to photographs.

Abstract: Individual differences in preferences to photographs were explored based on an alternative framework. This framework predicts that the primary difference between individuals in this respect is their ability to process photographic information, which in turn influences their preferences. Chiefly, people with well-developed schemes in photography (e.g., photo professionals) should have a higher ability to process photographic information than people with less developed schemes (e.g., psychology students). Conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 38 publications
5
52
3
Order By: Relevance
“…In the pilot study, 50 participants rated each photograph using 27 9-point semantic differential items based on Axelsson (2007). Before conducting the pilot study, we examined potential participants' understanding of how to use Axelsson's scale items through informal testing on comprehension of the terms used on the scales.…”
Section: Methodsmentioning
confidence: 99%
“…In the pilot study, 50 participants rated each photograph using 27 9-point semantic differential items based on Axelsson (2007). Before conducting the pilot study, we examined potential participants' understanding of how to use Axelsson's scale items through informal testing on comprehension of the terms used on the scales.…”
Section: Methodsmentioning
confidence: 99%
“…As Cupchik et al (2009) demonstrated, directing the viewer's attention to the artwork "In a subjective and engaged manner, experiencing the mood of the work and the feeling it evokes, and to focus on its colours, tones, composition, and shapes..." (p. 86) engaged the viewer in a different manner. And as previously noted, experience and expertise in art affects how art is processed (Axelsson, 2007;Cupchik & Gebotys, 1990;Eysenck & Castle, 1970;Hekkert et al, 1994;Hekkert & van Wieringen, 1996;Leder, Gerger, Dressler, & Schabmann, 2012;Schmidt, McLaughlin, & Leighten, 1989;Silvia, 2013;Winston & Cupchik, 1992). In future research, it would be worthwhile to decouple flexible cognitive control from instructional manipulations and expertise in order to properly assess whether flexible cognitive control is a significant factor in producing an aesthetic experience in the viewer of artworks.…”
Section: Discussionmentioning
confidence: 98%
“…Although a number of studies have shown that experts in art and novices in art judge aesthetic objects differently (Axelsson, 2007;Cupchik & Gebotys, 1990;Eysenck & Castle, 1970;Hekkert, Peper, & van Wieringen, 1994;Hekkert & van Wieringen, 1996;Leder, Gerger, Dressler, & Schabmann, 2012;Schmidt, McLaughlin, & Leighten, 1989;Silvia, 2013;Winston & Cupchik, 1992), we decided to focus on the naive viewer of art who does not have a formal background in photography or the visual arts. The reason we chose naive viewers was that they represent most of the viewers of art in real life situations.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Afterwards, participants listened to the four experimental sounds one more time and rated the perceived pleasantness, eventfulness, and familiarity on three bipolar category scales (Axelsson, 2007). Finally, the participants' threshold of hearing was tested, their audiogram was determined using an audiometer (Interacoustics Diagnostic Audiometer AD226, Hughson-Westlake method).…”
Section: Methodsmentioning
confidence: 99%